Digital transformaion in the oil and gas industry : how do unmanned aerial vehicles, specifically drones, contribute to improving the offshore inspection process of oil and gas platforms? - Kalb, Benedikt Michael (2019)
Regular inspections of oil and gas (O&G) platforms are vital for production, maintenance, safety, and the environment. Due to their location, offshore O&G facilities are exposed to hazardous and extreme conditions. In order to advance digitalization in the O&G sector, high-tech robots must be integrated. Traditional inspection methods, like Rope Access, Scaffolding, and Manned Helicopters imply significant challenges such as building scaffolding, sending inspection teams into hazardous environments, production downtime and high financial costs. Past research has identified how the introduction of unmanned aerial vehicles (UAVs) can meet the challenges by reducing costs, increasing safety conditions, increasing efficiency and improving accuracy. This dissertation presents the current state of research in the offshore O&G industry, identifies and quantifies cost and time factors. It compares the traditional inspection methods to the UAV inspection method by applying qualitative and quantitative methods of primary data gathering from industry expert interviews and secondary company data. This research shows that switching to UAV inspection allows a worldwide saving potential of USD 12B and market potential of USD 13M per inspection cycle. The complete Visual Inspection, including Flare, Underdeck, and Drilling Derrick is on average seven times faster than traditional methods. Introducing UAV inspection improves safety, as drone pilots operate up to 500m away from high-risk areas on the platform. Combining high-tech drones and AI-based software allows to generate a huge amount of data and build complete 3D models which can be reproduced continuously to detect trends in the state of the platform and apply Predictive Maintenance.